Literatura de cordel em rede: o fazer com tecnologias digitais - Cunha, Rafael da Silva da (2018)
Cordel literature is a literary genre that presents specific and particular rules as to the rhyme, metric, and structuring of texts. In its early days in Brazil, it was printed in leaflets and sold at fairs and railway stations in the Northeast region. Nowadays, with the advent of Information and Communication Technologies (ICT), new spaces of circulation of this poetic text were given, transcending its context that allowed it to go over its geographical limits. On the Internet, for example, websites, blogs and social media pages can be used for the production and dissemination of cordel literature. In addition, different resources are available enabling stringers to compose their works, such as images, sounds and hyperlinks, eliciting new ways of doing string literature, and it is important to understand them. Thus, the present research aimed to understand how the mediation of digital technologies influence the writing process of cordel literature, enhancing new cognitive experiences. We start from the assumption that the coupling of human beings with technical objects determines a creative inner process that can be seen as the process of knowing itself. We understand that doing stringed literature with digital technologies can provoke displacements and transformations in the ways of writing and in the poetic writing itself. The theoretical support network was woven from the contributions of Albuquerque Junior about the invention of northeaster popular culture; Roger Chartier thinking above the popular culture notion and changes in the ways of writing from the integration of technologies; Pierre Lévy and Gilbert Simondon understanding of the relation between humanity and technical objects; and the studies of writing in the convergence of media from Karla Demoly. In a qualitative approach, we use virtual ethnography as a research method. The techniques to obtain the information consisted of research and selection of websites, blogs and social networks that disseminate cordel literature; observations in the selected pages and interviews with the cordel writers who manage their poetic production; analysis and discussion of information. This methodology enabled us to understand the dynamics of cordel literature in cyberspace, fomenting discussions about writing mediated by digital technologies. We find that cordel literature is surpassing a moment of transgression among textual support. In reaching the cyberspace, the cordel writers began to integrate texts, sounds and images, and to expand the thematic universe of the genre, adopting specific creation strategies for the virtual environment. These alterations in the modes of writing and in the cordelistic work itself are perceptible in our analyzes, and recognized by the cordel writers interviewed